4CPS-211 Evaluation of the interventions of a critical care pharmacist in addition to team-based care in an intensive care unit. (2nd March 2018) - Serramontmany, E; Girona, L; Juarez, JC; Robles, A; Riveiro, M; Betriu, L; Lalueza, P
Abstract : Background: A pharmacist in the intensive care unit (ICU) as a component of multi-professional staff may improve the care provided to patients, particularly by monitoring the drugs administered, reducing preventable adverse drug events (ADE) and identifying drug interactions and errors. Purpose: Evaluate the interventions of a critical care pharmacist (CCP) as a component of team-based care in a Spanish neurotrauma ICU (NTICU). Material and methods: Prospective observational study with patients admitted in a NTICU for 5 weeks (including only working days). CCP collaborates with a multidisciplinary team selecting the medication therapy, dosage, duration and monitoring, based on physician diagnosis and team's goals for the patient. CCP is also responsible for clinical services and electronic verification of medication orders. Results: Out of 54, only 42 patients were monitored, with a mean age of 57 years (31–85), of which 31 were males (74%). Eleven patients were admitted for polytrauma (26%), eight for severe traumatic brain injury (19%), six for acute spinal cord injury (14%), three for cerebrovascular accident (7%), two for necrotising fasciitis (5%) and 12 (28%) for other causes. The median days of admission were 14. There were only five deaths during the study period. A total of 116 interventions were done, almost three interventions per patient and five per day of dedication of the CCP. The majority of interventions were related to artificial nutrition monitoring (28) and about the management of antimicrobial optimisation (27): nine discontinuations of antibiotic prophylaxis, six antibiotic dose adjustments, four recommendations to de-escalate the antibiotic and three antibiotic changes because they did not cover the pathogen. Twenty-two interventions were related to drug administration, 11 with conciliation, eight with intravenous-to-enteral conversion, five of thromboembolism prophylaxis, four drug-related questions, three discontinuations by duplications, two stopped because of ADE and one interaction. According to an internal hospital protocol, 26% of interventions were considered of high clinical impact. Conclusion: As most of the interventions were related to artificial nutrition adjustments, antimicrobial optimisation management and drug administration, a checklist was designed, containing such points where the pharmacist is mostly involved, to monitor critical patients in a standardised way and to simplify the detection of discrepancies. References and/or Acknowledgements: Thanks to all authors for their involvement. No conflict of interest